Tinjauan Yuridis Perbuatan Ingkar Janji (Wanprestasi) Oleh Buruh Tani Ditinjau Dari Kompilasi Hukum Ekonomi Syariah - Khairani, Elfida; Harahap, Ikhwanuddin; Harahap, Nurhotia (Jurnal El-Thawalib, 2023)
The problem in this research is about the practice of broken promises (defaults) by farm workers in the village of Lumban Dolok. This type of research is field research. The primary data source in this study is by conducting direct interviews with farm workers who own the plantation, the Head of Lumban Dolok Village, traditional leaders. while the secondary data is in the form of fiqh muamalah books, and journals related to this research. Data collection techniques using field studies, namely observation, interviews, and documentation. The data analysis technique used in this study is to use a qualitative descriptive method. The results of the study show that the act of breaking a promise (default) by this farm worker begins with a verbal agreement between the owner of the garden and the farm worker in the agreement, one of the points is not being able to cancel the agreement suddenly and not asking for wages before doing the work. . However, in reality, when he was about to implement the farm labor agreement, he canceled the agreement with the garden owner, and asked for his wages on the grounds that he really needed it. This practice of breaking promises (defaults) by farm workers when viewed from a juridical view of this agreement is considered a unilateral cancellation of the agreement without the consent of the other party, in accordance with Article 1338 paragraph (2) of the Civil Code, it is clear that the agreement cannot be canceled unilaterally, because if the agreement is canceled unilaterally, it means that the agreement is not binding between the people who made it. Meanwhile, if viewed from the compilation of sharia economic law, it is explained in article 36 which explains that breaking a promise occurs if you do not do what has been promised, in this case the farm worker does not carry out the agreement in accordance with the agreement and terminates the agreement suddenly without any clear reason. This also contradicts the compilation of sharia economic law article 21 which states that there is no trustworthiness from farm workers, besides that there is also no attitude of openness and good faith from farm workers to find a replacement to be able to continue the agreement that has been canceled.